A spear to the heart—the accidental discovery of a giant cement embolism in the right heart: a case report. Issue 11 (25th August 2021) - Lambers, Moritz; Bruder, Oliver; Wieneke, Heinrich; Nassenstein, Kai
Abstract: Background: The incidence of recognized cardiopulmonary cement embolism in the context of percutaneous vertebroplasty varies between 0% and 23%. In most cases, only small fragments embolize in the pulmonary arteries or the right heart cavities. The latter can cause potential harm by right ventricular perforation. Case summary: A 57-year-old patient was admitted to our department of cardiology due to exertional dyspnoea and chest pain. In the course of further diagnostic tests, a huge cement embolus was accidentally discovered in the right ventricle. The unusual size and length and the threat of ventricular perforation make this case so unique. Discussion: Large cement embolisms in kyphoplasty settings are possible and associated with the risk of fulminant complications.